2022
DOI: 10.1038/s41589-022-01074-8
|View full text |Cite
|
Sign up to set email alerts
|

A modification-centric assessment tool for the performance of chemoproteomic probes

Abstract: Chemoproteomics has emerged as a key technology to expand the functional space in complex proteomes for probing fundamental biology and for discovering new small molecule-based therapies. Here we report a modification-centric computational tool termed pChem to provide a streamlined pipeline for unbiased performance assessment of chemoproteomic probes. The pipeline starts with an experimental setting for isotopically coding probe-derived modifications (PDMs) that can be automatically recognized by pChem, with m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 84 publications
4
15
0
Order By: Relevance
“…Therefore, most if not all STY-cross-link identification are unreliable. This is consistent with a recent finding that a pair of light/heavy isotope-labeled NHS ester probes did not label protein/ peptides at STY residue 46 . It is also supported by an earlier finding that at pH 6.7 and pH 7.8, no detectable reaction products were found between an NHS ester cross-linker and peptide hydroxyl groups of STY residues, even after 24 hours 30 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, most if not all STY-cross-link identification are unreliable. This is consistent with a recent finding that a pair of light/heavy isotope-labeled NHS ester probes did not label protein/ peptides at STY residue 46 . It is also supported by an earlier finding that at pH 6.7 and pH 7.8, no detectable reaction products were found between an NHS ester cross-linker and peptide hydroxyl groups of STY residues, even after 24 hours 30 .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the above conclusion, a recent proteome-scale study has found no evidence of a NHS ester probe targeting S, T, or Y 46 . In this study, a HeLa cell lysate was incubated with a pair of light and heavy isotope encoded NHS ester probe, and pChem-a software tool developed specifically to assign modification sites of chemical probes-was employed to analyze the data.…”
Section: Resultssupporting
confidence: 73%
“…Here we envisioned combining proximity labeling via the ultra-fast biotin ligase TurboID with cysteine chemoproteomics 11,21,[24][25][26][27][28][29][30]57,58 to enable fractionation-free capture of the subcellular cysteinome, for both residue identification and quantification of cysteine oxidation. We were inspired by recent reports of two-step capture for subcellular phosphoproteomics, in which proteins biotinylated by TurboID were first enriched on avidin resin followed by peptide-level capture of phosphopeptides 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Application of these methods have pinpointed cysteines differentially oxidized in association with high levels of ROS and RNS, such as those of TRX 13,14 , GAPDH 15,16 and HBB 17 . Given the recent advent of cysteine-reactive small molecules as precision therapies for the treatments of cancers and immune disorders [18][19][20] , cysteine chemoproteomic methods have also emerged as enabling technology for pinpointing ligandable or potentially 'druggable' residues proteome-wide [21][22][23][24][25][26][27][28][29][30] . A central remaining challenge for these studies is the lack of a priori knowledge about the functional impact of covalent modification.…”
mentioning
confidence: 99%
“… The RBR-ID method does not include a dedicated enrichment step, but compares peptide intensities between cross-linked samples prepared with 4-thiouridine(4-SU)-labelled RNA and non-cross-linked samples. The mass shift introduced by covalently bound RNA will lead to a decrease in signal for successfully cross-linked peptides between the two samples [ 15 ]. 2C (silica-based solid-phase extraction), TRAPP (total RNA-associated protein purification), and RBS-ID utilise silica beads/membranes for nucleic acid enrichment [ 16 , 17 ].…”
Section: Approaches To Study the Rbpomementioning
confidence: 99%